Implications and Challenges of Implementing PSAK 22 Convergence with IFRS 3 on Goodwill Accounting in Indonesia - Widiyati, Dian; Ramadhani, Annisa Syarifah (Jurnal Riset Akuntansi dan Auditing, 2025)
This study aims to identify the implication and challenge of implementing PSAK 22 Convergence of IFRS 3 on goodwill accounting in Indonesia. PSAK 22 which is converged with IFRS 3 regulates business combinations, including the recognition and measurement of goodwill, with a focus on the exception of amortization and the application of impairment tests (impairment tests). The research method used is the Systematic Literature Review (SLR) with an analysis of 11 related articles to elaborate on the main issues in the implementation of PSAK 22. The results of the study indicate that the implementation of PSAK 22 increases the transparency of financial statements and the relevance of information for stakeholders. On the other hand, there are challenges in implementing PSAK 22 such as the complexity of fair value measurement, high implementation costs, and managerial discretion that can affect reporting reporting. This study contributes to the literature on the implementation of PSAK 22 in Indonesia by offering insights into the benefits and challenges faced by entities in implementing this standard. The novelty lies in reviewing PSAK 22 implementation in Indonesia, highlighting implications and challenges in goodwill accounting, and providing insights on IFRS 3 convergence benefits and difficulties within Indonesia’s accounting environment. Abstrak - Penelitian ini bertujuan untuk mengidentifikasi implikasi dan tantangan penerapan PSAK 22 yang terkonvergensi dengan IFRS 3, khususnya terkait pengakuan dan pengukuran goodwill di Indonesia. Metode penelitian yang digunakan adalah systematic literature review (SLR) dengan analisis terhadap 11 artikel terkait untuk mengelaborasi isu-isu utama dalam penerapan PSAK 22. Hasil penelitian menunjukkan bahwa implementasi PSAK 22 meningkatkan transparansi laporan keuangan dan relevansi informasi bagi pemangku kepentingan. Di sisi lain, terdapat tantangan dalam implementasi PSAK 22 seperti kompleksitas pengukuran nilai wajar, biaya implementasi yang tinggi, dan diskresi manajerial yang dapat memengaruhi keandalan pelaporan. Penelitian ini memberikan kontribusi terhadap literatur tentang implementasi PSAK 22 di Indonesia dengan menawarkan wawasan mengenai manfaat dan hambatan yang dihadapi oleh entitas dalam melaksanakan standar ini. Kebaruan penelitian ini terletak pada kajian implementasi PSAK 22 di Indonesia, yang menyoroti implikasi dan tantangan dalam akuntansi goodwill serta memberikan wawasan tentang manfaat dan kesulitan konvergensi IFRS 3 dalam lingkungan akuntansi Indonesia.